2012 IMJ Reviewers (Internal Medicine Journal, 2013)
Australian general medicine perioperative services provide care to surgical patients with complex comorbidities, for a wide range of medical conditions. Heterogeneous models of care exist; however, their cost-consequence has not been evaluated. Cost analysis was conducted using nationally standardised cost weights for length of stay, medical emergency team call costs and labour costs. Proactive models of general medicine perioperative care likely save approximately $7500 per patient compared with reactive models.